2004
DOI: 10.1645/ge-333r
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasites and Other Epifaunistic Arthropods of Sympatric Cotton Mice and Golden Mice: Comparisons and Implications for Vector-Borne Zoonotic Diseases

Abstract: Ectoparasite and epifaunistic arthropod biodiversity and infestation parameters were compared between 2 sympatric small rodent species, the cotton mouse (Peromyscus gossypinus (Le Conte)) and golden mouse (Ochrotomys nuttalli (Harlan)), in southern Georgia from 1992 to 2003. Because the cotton mouse is known to be a reservoir of more vector-borne zoonotic pathogens than the golden mouse, we hypothesized that it would be parasitized by more ectoparasites that are known to be vectors of these pathogens. Cotton m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Taken together, ectoparasite communities and associated (zoonotic) pathogens of various wildlife rodent species represent a well-studied issue [ 8 , 9 ], but in this context much less is known about synanthropic rodents (although these could be more relevant to assess from the point of view of zoonotic vector-borne pathogens). Therefore, the present study was undertaken to elucidate if (hemi)synanthropic rodents and their blood-sucking ectoparasites are infected with five important categories of vector-borne pathogens (haemoplasmas, rickettsiae, Anaplasmataceae, Borrelia burgdorferi sensu lato [s.l.]…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, ectoparasite communities and associated (zoonotic) pathogens of various wildlife rodent species represent a well-studied issue [ 8 , 9 ], but in this context much less is known about synanthropic rodents (although these could be more relevant to assess from the point of view of zoonotic vector-borne pathogens). Therefore, the present study was undertaken to elucidate if (hemi)synanthropic rodents and their blood-sucking ectoparasites are infected with five important categories of vector-borne pathogens (haemoplasmas, rickettsiae, Anaplasmataceae, Borrelia burgdorferi sensu lato [s.l.]…”
Section: Resultsmentioning
confidence: 99%
“…Las comunidades de ectoparásitos y patógenos de diferentes especies de roedores de vida silvestre se han estudiado extensamente (17,18), pero muy poco se conoce sobre las especies de roedores sinantrópicos. Los roedores sinantrópicos, como el ratón de casa (Mus musculus) y la rata negra (Rattus rattus), son especies asociadas a las viviendas y a sistemas agrícolas y pecuarios.…”
unclassified
“…Newson & Holmes (1968) reported that P. coypus were found on coypus of all ages and both sexes throughout the year, but Feldhamer et al (2003) reported that season appeared to modulate the rate of infestation, with the highest incidence occurring in late winter. Perhaps conditions of the host pelage or of the microhabitats inside the host nests may influence off-host survival and reproduction for the parasite (DURDEN et al, 2004).…”
Section: Discussionmentioning
confidence: 99%